2011
DOI: 10.1093/annonc/mdq417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SCA instrument for measuring patient satisfaction with cancer care administered via paper or via the Internet

Abstract: Background: Patients’ perspectives provide valuable information on quality of care. This study evaluates the feasibility and validity of Internet administration of Service Satisfaction Scale for Cancer Care (SCA) to assess patient satisfaction with outcome, practitioner manner/skill, information, and waiting/access.Patients and methods: Primary data collected from November 2007 to April 2008. Patients receiving cancer care within 1 year were recruited from oncology, surgery, and radiation clinics at a tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…We measured cancer care satisfaction using the Satisfaction Scale for Cancer Care (SCA), developed and validated by our group and previously described [15,17]. Unlike other instruments focused on satisfaction with cancer care processes, the SCA instrument is unique in providing a robust, valid measure of satisfaction with care outcome (Cronbach α = 0.88) [18].…”
Section: Methodsmentioning
confidence: 99%
“…We measured cancer care satisfaction using the Satisfaction Scale for Cancer Care (SCA), developed and validated by our group and previously described [15,17]. Unlike other instruments focused on satisfaction with cancer care processes, the SCA instrument is unique in providing a robust, valid measure of satisfaction with care outcome (Cronbach α = 0.88) [18].…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, reliable and validated instruments for the evaluation and assessment of the patient satisfaction were published and were given to patients [5,16,17,18,28,36]. A crucial determinant for patient satisfaction is communication between physician and patient [5].…”
Section: Patient Satisfaction During Radiation Therapy Correlates Andmentioning
confidence: 99%
“…For study purposes subjects were explicitly asked which sources they used and which they found most helpful. SCA, a reliable and responsive instrument adapted from the Service Satisfaction Scale, 15,16 was used to measure patient satisfaction with information during followup. SCA consists of 16 items measuring patient satisfaction across several treatment related domains, including 3 that measure satisfaction with information used to make treatment related decisions.…”
Section: Methodsmentioning
confidence: 99%